2020
DOI: 10.1177/1120672120944798
|View full text |Cite
|
Sign up to set email alerts
|

Corneal biomechanical outcome of collagen cross-linking in keratoconic patients evaluated by Corvis ST

Abstract: Purpose: A 6-month evaluation of the topographic and biomechanical changes induced by corneal collagen cross-linking (CXL) in keratoconic eyes using Pentacam and Corvis ST. Design: Longitudinal prospective case series. Methods: In this study, 67 eyes of 67 patients with progressive keratoconus (KCN) treated with “Epithelium-off” CXL were evaluated. Patients with stages 1 or 2 of KCN and a corneal thickness of at least 400 μm at the thinnest point were included. Standard ophthalmologic examinations were carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 43 publications
4
24
0
Order By: Relevance
“…Clinical results showed that SP-A1 increased significantly 6 months after CXL [22], and no significant changes was found 4 years after CXL [23]. In this study, SP-A1 was increased immediately after CXL, which was in agreement with the reported increase of corneal elastic properties from a short-term evaluation in vivo after CXL.…”
Section: Discussionsupporting
confidence: 91%
“…Clinical results showed that SP-A1 increased significantly 6 months after CXL [22], and no significant changes was found 4 years after CXL [23]. In this study, SP-A1 was increased immediately after CXL, which was in agreement with the reported increase of corneal elastic properties from a short-term evaluation in vivo after CXL.…”
Section: Discussionsupporting
confidence: 91%
“…One study compared different CXL treatment protocols and found a significant increase of SP-A1 in 21 patients who underwent accelerated CXL (9 mW/cm 2 , as in this study) 16. This finding was also observed in another study that assessed 67 corneas with mild KC 6 months after CXL 12. A third study, however, did not find a change of SP-A1 in 18 patients that were followed-up for up to 4 years after CXL according to the Dresden protocol 13.…”
Section: Discussionsupporting
confidence: 86%
“…Strengths of the current study include the analysis of keratoconic and postkeratoplasty eyes, which has previously not been conducted after nonfenestrated scleral lens wear, and the use of the CORVIS ST instrument, which seems to be able to consistently detect changes in corneal biomechanical properties compared with other instruments (e.g., after corneal collagen cross-linking). 24,36,37 Limitations of the current study include the relatively short duration of lens wear (8 hr) in comparison to typical scleral lens wearing times (e.g., 12 hr or more per day, on a full time basis) 38 and the relatively small sample of postpenetrating keratoplasty eyes. Future studies using newer metrics to quantify corneal biomechanics may reveal new insights into potential scleral lens-induced corneal changes; 23,39–41 however, it should be noted that currently there is no method available to assess corneal biomechanics or IOP during scleral lens wear, which may differ to measurements obtained after lens removal.…”
Section: Discussionmentioning
confidence: 98%